2020
DOI: 10.1021/acsapm.0c00006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Metal Ion-Sensing Properties of Isomeric Crystalline Polyacylhydrazone Organogelators

Abstract: Two isomeric polyacylhydrazones P-1 and P-2 were prepared by dynamic covalent chemistry. Due to the presence of aromatic moieties and intramolecular hydrogen bonds in the backbone, both polymers exhibited very high crystallinity. Furthermore, they had shown to be very strong physical gelators for aromatic solvents. Upon interacting with metal ions, the two polymers demonstrated different yet specific metal ion-responsive properties such as gel-to-sol transition, gel strength reinforcement, and/or quenching/enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This result was consistent with the descriptions described in the literature. [ 38 ] Additionally, the comparison of three configurations of aromatic polyacylhydrazone showed that there was little difference in their fluorescence, and the fluorescence intensity of polyacylhydrazone from p ‐phthalaldehyde was slightly higher, possibly due to its symmetrical structure. In brief, the aliphatic polyacylhydrazone provided more characterization and performance regulation as subsequently described.…”
Section: Resultsmentioning
confidence: 99%
“…This result was consistent with the descriptions described in the literature. [ 38 ] Additionally, the comparison of three configurations of aromatic polyacylhydrazone showed that there was little difference in their fluorescence, and the fluorescence intensity of polyacylhydrazone from p ‐phthalaldehyde was slightly higher, possibly due to its symmetrical structure. In brief, the aliphatic polyacylhydrazone provided more characterization and performance regulation as subsequently described.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Fang et al fabricated a tetraphenylethylene-based acylhydrazone gel for luminescence sensing of Cu 2+ and subsequent CN − detection [ 47 ]. Similarly, Wang et al reported two crystalline polyacylhydrazone organogels whose fluorescence could respond to metal ions [ 48 ]. Very recently, the Tang group reported a phototriggered AIE (PTAIE) acylhydrazone gel which could be used for 4D soft patterns [ 49 ].…”
Section: Polymeric Emissive Materials Based On Acylhydrazone Bondmentioning
confidence: 99%
“…1–3 One unique feature is that the physiochemical properties of supramolecular nanostructures can be facilely controlled via the molecular-level design of self-assembling building blocks. For example, the morphologies of peptide assemblies are highly sequence-specific 4–6 and sensitive to the amino acid position in isomeric peptide sequences. 7–9 In other examples, the self-assembly behavior of monomeric building blocks is controlled by the attachment and removal of enzyme cleavable pendant functional groups, enabling the sol–gel transition of supramolecular materials.…”
Section: Introductionmentioning
confidence: 99%